1995
DOI: 10.1152/jappl.1995.78.6.2245
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion molecules contribute to ischemia and reperfusion-induced injury in the isolated rat lung

Abstract: Leukocyte adherence to the endothelium after ischemia and reperfusion contributes to microvascular injury in most organs. The purpose of this study was to evaluate the leukocyte and endothelial cell adhesion molecules involved with ischemia-reperfusion (I/R)-induced pulmonary microvascular injury in the isolated rat lung. After 45 min of ischemia and 30 min of reperfusion, microvascular permeability was significantly increased and lung retention of leukocytes occurred. Pretreatment with monoclonal antibodies a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
66
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(70 citation statements)
references
References 0 publications
4
66
0
Order By: Relevance
“…To our knowledge, we provide the first direct evidence that high pressure induces P-selectin expression in lung microvessels, a finding that is relevant to mechanisms of lung injury. P-selectin is implicated in such mechanisms, because lung injury after complement activation or ischemia-reperfusion is attenuated by anti-P-selectin antibody (42,43). In stimulated endothe- lial cells, P-selectin is rapidly internalized (16) and either sorted to the Golgi (35) and WP bodies for receptor reexpression (44) or targeted to lysosomes in order to prevent recycling (36).…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, we provide the first direct evidence that high pressure induces P-selectin expression in lung microvessels, a finding that is relevant to mechanisms of lung injury. P-selectin is implicated in such mechanisms, because lung injury after complement activation or ischemia-reperfusion is attenuated by anti-P-selectin antibody (42,43). In stimulated endothe- lial cells, P-selectin is rapidly internalized (16) and either sorted to the Golgi (35) and WP bodies for receptor reexpression (44) or targeted to lysosomes in order to prevent recycling (36).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence against this role includes findings that P-selectin-inhibitory mAb does not block leukocyte rolling in venules (26) and that bacteria-induced leukocyte migration is not inhibited in P/E-selectin-knockout mice (27). Evidence supporting a role for P-selectin includes findings that P-selectin-blocking mAbs inhibit ALI induced by cobra venom (28) or ischemia-reperfusion (29) and that P-selectin-knockout mice are protected from ALI due to ischemia-reperfusion (30). We reported that P-selectin accounts for the pressure-induced leukocyte accumulation (6), thereby implying a role for P-selectin in the proinflammatory phenotype induced by pulmonary venous hypertension.…”
Section: Mitochondrial Buffering It Is Proposed That Mitochondria Bumentioning
confidence: 99%
“…It is not well documented whether, at the same time, acute hypoxia also induces changes at the level of pulmonary inflammatory mediators. Most of the in vivo studies performed to date have concentrated on ischemia-reperfusion injury in organs (15,18). However, the direct effects of hypoxia without reperfusion on tissue have not been well explored.…”
mentioning
confidence: 99%